(untitled) (Environment & Health, 2018)
Background: Features of ambient air pollution at the border of the sanitary protection zone and the residential area with the emissions from modern powerful pig complexes are considered in the example of the pig complex with an annual capacity of 30 thousand heads. Objective: We assessed the ambient air pollution with the emissions from livestock farms in the example of the farms for pigs’ breeding (pig complexes) with a capacityof 30 thousand heads per year. Materials and methods: We used the method of bibliographic and bibliosemantic search; we performed field instrumental measurements of the concentration of the pollutants in the emissions from stationary sources of contamination of the pig complexes and in ambient air of the settlements. Results: The maximum concentrations of pollutants in the content of the emissions of pig complex (hydrogensulphide, ammonia, solidsuspended particles (PM)) were established not to exceed the maximum allowable emission. The average concentrations of the pollutants in ambient air in terms of the maximum single maximum allowable concentration (MPCotm) are exceeded only by hydrogensulfide (at a distance of upto 200 m - 2.5 MPCotm, at a distance of 500 m - 2.4 MPCotm, at 1000 m - 5 MPCotm), no excesses for other substances (ammonia, PM) were detected. Conclusions: The obtained results testify about absence of ambient air pollution with ammonia and PM emissions from pig complexes and its pollution with hydrogensulphide in concentrations, exceeding MPCotm, depending on distance (200, 500 and 1000 m). In addition, the obtained results make it possible to reduce the normative sizes of sanitary-and-protective zones of livestock complexes under condition of the use of modern production technologies for the maintenance and fattening of pigs, the organization of the production ventilation systems and the technological process of livestock breeding which reduce the emission of hydrogensulfide to the level of the standard MPCotm.